1997
DOI: 10.1021/ac970353p
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin-Modified Electrodes as Biomimetic Sensors for the Determination of Organohalide Pollutants in Aqueous Samples

Abstract: A preliminary examination of a simple and rapid screening method for quantifying a range of toxic organohalides directly in aqueous solution based on their electrocatalytic reduction with a metalloporphyrin catalyst is described. Homogenous catalysis is described as well as heterogeneous catalysis using precipitated cobalt(II) tetraphenylporphine ((TPP)Co) at a graphite foil electrode which permitted the sensitive detection of a wide range of different organohalides, including a number of chemically diverse in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 42 publications
2
33
1
Order By: Relevance
“…The electrochemical properties of MOFs have recently received significant attention in the chemical literatures 14. MOFs constructed with porphyrin subunits are particularly interesting because of their redox activity and have been tested as electrodes to detect organohalide pollutants,15 oxygen,16 and thrombin 17. The MOF architecture is important because these porphyrin‐based materials such as MOF‐525 have high specific surface areas, and the electrochemical activity of the porphyrin subunit can be tuned for different electrochemical sensing applications 18.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical properties of MOFs have recently received significant attention in the chemical literatures 14. MOFs constructed with porphyrin subunits are particularly interesting because of their redox activity and have been tested as electrodes to detect organohalide pollutants,15 oxygen,16 and thrombin 17. The MOF architecture is important because these porphyrin‐based materials such as MOF‐525 have high specific surface areas, and the electrochemical activity of the porphyrin subunit can be tuned for different electrochemical sensing applications 18.…”
Section: Introductionmentioning
confidence: 99%
“…Beside immobilized iron and manganese porphyrins, cobalt complexes were also been investigated due to their promising functions as catalysts or selective complexing centers via axial ligation reactions. The latter were, for instance, successfully exploited for the study of phenol interaction [13], oxygen or NO reduction [14,15] and the detection of organohalide pollutants or nitrite [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…By immobilizing such complexes on the electrode surface, one may take profit from their electrocatalytic capabilities to conceive new analytical tools for the detection of organic halides in solution. Examples describing the use of modified electrodes based on porphyrin and Schiff base complexes, which have been immobilized by different physical ways (adsorption, chemical condensation or incorporation in an organic glue, electropolymerization) has been reported only recently [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The flow injection analysis of 2,4-dichlorophenoxy acetic acid and 2,2-dichloroacetic acid showed that the response of the modified electrode was enhanced 50 times compared to the bare electrode. More recently, Dobson and Saini [11] reported the detection of different organohalides, including a number of industrial pollutants, by using a modified electrode consisting in a graphite foil covered with adsorbed cobalt porphyrin. The authors provided significant results on the detection of three classes of halides by amperometric measurements.…”
Section: Introductionmentioning
confidence: 99%